Social prescribing in rural settings: A mapping review of benefits, challenges, and implementation strategies for rural Australia - Imran Saddiq; Peter Simmons; Uchechukwu Levi Osuagwu (Social Sciences and Humanities Open)
Background: Social prescribing (SP) models, which connect individuals to non-medical community-based services, are widely established in the UK and Europe, yet remain in early development stages in Australia. SP is commonly but informally practiced by healthcare professionals in Australia, and despite promising results in other countries there is limited empirical evidence of its effectiveness in Australia, particularly in rural contexts. This study aimed to review the literature on SP in rural contexts, identifying benefits, challenges, and logistical considerations for establishing formal SP programs while highlighting gaps to guide future research. Methods: This mapping review followed the PRISMA extension for scoping reviews. A systematic search across MEDLINE (Ovid), EMBASE, and CINAHL was conducted from July 5th to 7th, 2024, yielding 145 articles. After duplicate removal and screening, 27 articles underwent full-text review. Thematic analysis identified key themes relevant to SP in rural contexts. Results: Three main themes were identified: benefits of SP, logistical considerations, and challenges in rural settings. SP positively impacted rural health issues such as loneliness, social isolation, and mental health. Logistical factors included the importance of the link worker model and engagement with local community groups. Various SP delivery modes (online, face-to-face, hybrid) were identified, each with unique advantages. Key challenges included inadequate funding, limited-service availability, and insufficient training for link workers and stakeholders. Conclusion: Social prescribing shows considerable promise in addressing health challenges and improving health outcomes in rural Australia, but success will depend on overcoming significant logistical, financial, and training challenges. Future research should focus on developing tailored, scalable SP models for rural communities.